Deep HI observations of nearby late-type galaxies - Sorgho, Amidou (Department of Astronomy, 2020)
This thesis makes use of sensitive Hi observations to map the distribution and kinematics of the low column density neutral hydrogen in late-type nearby mostly isolated galaxies and in the nearby M81 group. Using the KAT-7, GBT and MeerKAT AR1 telescopes, we present in the second chapter a survey of the Hi in a sample of twenty nearby, mostly isolated galaxies down to low column density levels. This provided a new Hi view of some of these galaxies, which allowed to derive their kinematics out to unprecedented extents. Despite the short spacings of KAT-7 and MeerKAT AR1, and the large size of the single-dish GBT that make these telescopes ideal for detecting faint structures, the observations revealed no clear detection of low column density Hi clouds down to a typical sensitivity of ∼2.2 × 1018 cm−2 that could be associated to gas accretion in the observed galaxies. However, we do not discard the existence of such structures that, we note, could be in the form of discrete clouds smaller than the beam size of the telescopes. In the third chapter, we use the DRAO telescope to perform a sensitive survey of the Hi in a 5 ◦ × 5 ◦ area of the M81 group. Similarly to previous observations, we find that the three major and interacting galaxies of the group – M81, M82 and NGC 3077 – are connected through Hi bridges and intergalactic Hi clouds. One of the major findings of the survey is the more complete map of the western Hi arm connecting the three galaxies to the dwarf galaxy NGC 2976. These observations offer enough resolution to map the structure of the arm, and reveal a complex of small clouds filling the space between the arm and the Hi forming “main body” of the interacting galaxies. Using a tilted-ring model, we also construct a large-scale rotation curve of the system formed by the interacting galaxies. Consistently with the large-scale velocity field, we observe a flat trend for the rotation velocity of the system from 20 kpc out to 80 kpc, well beyond the outskirts of the M81 disk, although with asymmetries like a wiggle at the vicinity of M82. The fourth chapter focuses on a subset of the M81 survey containing the dwarf galaxy IC 2574 and the Hi complex HIJASS J1021+68. In this chapter we perform a thorough analysis of the distribution and kinematics of the Hi in the two systems, and thanks to the high sensitivity we are able to detect a substantially large amount of low column density Hi around IC 2574, in the form of an Hi envelope, and in two large concentrations around the galaxy. We find evidence that HIJASS J1021+68 – which is found to be connected to IC 2574 through a filament of discrete clouds – is not a dark galaxy as previously suggested, but is instead a complex of clouds either stripped from, or falling onto the primordial Hi envelope of IC 2574. The kinematical analysis of IC 2574 using a 3D tilted-ring model brings us to derive its rotation curve out to a larger extent than previous works and allows us to constrain its Dark Matter halo parameters, which we find consistent with the literature. Overall, the different results presented in this work prove that the Hi content of local galaxies is higher than what current observations reveal, and new sensitive telescopes such as MeerKAT and the upcoming SKA will unveil a new Hi view of galaxies.